2019
DOI: 10.1210/clinem/dgz045
|View full text |Cite
|
Sign up to set email alerts
|

The Risks of Cardiovascular Disease and Mortality Following Weight Change in Adults with Diabetes: Results from ADVANCE

Abstract: Context Weight loss is strongly recommended for overweight and obese adults with type 2 diabetes. Unintentional weight loss is associated with increased risk of all-cause mortality, but few studies have examined its association with cardiovascular outcomes in patients with diabetes. Objective To evaluate 2-year weight change and subsequent risk of cardiovascular events and mortality in established type 2 diabetes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 52 publications
0
28
0
2
Order By: Relevance
“…Unintentional body weight loss is another potential risk factor for cardiovascular diseases and mortality. In a secondary analysis of the ADVANCE study, an interventional trial of patients with diabetes, the risk for cardiovascular diseases and mortality doubled in those with unintentional body weight loss of > 10% compared to those without apparent body weight change (between −4% and 4%); the finding was independent of age [112]. Unintentional weight loss is a diagnostic criterion for frailty based on the CHS; therefore, body weight should be regularly monitored for early detection of even a slight weight reduction.…”
Section: Changes In Body Weightmentioning
confidence: 97%
“…Unintentional body weight loss is another potential risk factor for cardiovascular diseases and mortality. In a secondary analysis of the ADVANCE study, an interventional trial of patients with diabetes, the risk for cardiovascular diseases and mortality doubled in those with unintentional body weight loss of > 10% compared to those without apparent body weight change (between −4% and 4%); the finding was independent of age [112]. Unintentional weight loss is a diagnostic criterion for frailty based on the CHS; therefore, body weight should be regularly monitored for early detection of even a slight weight reduction.…”
Section: Changes In Body Weightmentioning
confidence: 97%
“…Model 2: Model 1 + further adjusted for BMI, educational level, current smoking (at first follow-up), GLD use (at baseline or first follow-up), family history of premature CVD, hypertension, hypercholesterolemia, CKD, and FPG CHD coronary heart disease, BMI body mass index, GLD glucose-lowering drugs, CVD cardiovascular disease, CKD chronic kidney disease, FPG fasting plasma glucose [13]. Based on results from the ADVANCE trial, compared to a stable weight, 2-year weight loss > 10% was associated significantly with increased risk of major cardiovascular events and CVD mortality; in contrast, weight gain did not contain a significant effect on CVD [16]. Recently, among about 20,000 White British UK biobank participants with T2DM, it was shown that the minimum mortality risk was seen in those with a BMI of 32 kg/m 2 ; moreover, using Mendelian randomization, the researchers did not find a significant impact of obesity on mortality in this population [27].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of prospective studies, despite a high heterogeneity, weight loss increased the risk of CVD mortality by 15% among overweight or obese patients with diabetes; moreover, weight gain had a HR of 0.97 [0.93–1.01] [ 13 ]. Based on results from the ADVANCE trial, compared to a stable weight, 2-year weight loss > 10% was associated significantly with increased risk of major cardiovascular events and CVD mortality; in contrast, weight gain did not contain a significant effect on CVD [ 16 ]. Recently, among about 20,000 White British UK biobank participants with T2DM, it was shown that the minimum mortality risk was seen in those with a BMI of 32 kg/m 2 ; moreover, using Mendelian randomization, the researchers did not find a significant impact of obesity on mortality in this population [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations